Analysis Of Language Acquisition in The Qur'an Psycholinguistic Perspectives in Education - Irfan Sunaryo; Nur Hidayat; Rusdy Iskandar; Lusi Oktavia; Nurul Huda; Afifah Rizki (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
This study aims to investigate language acquisition in the Qur'an in more detail from a psycholinguistic perspective. A psycholinguistic lens is used to explore language in this article. This study chose a descriptive qualitative approach as the research methodology. The literature review uses the data source, which looks for data sources in papers and books from scientific journals related to the previous research. The data collection method used in this research is a library or literature review. The material to be observed is journal articles that discuss language acquisition in the Qur'an from a psycholinguistic perspective. According to the findings of this study, Arabic is the language of religion and international communication in the current global era. Therefore, it cannot be denied that learning Arabic is very important for understanding religious teachings, especially the teachings contained in the Qur'an. Psycholinguistic understanding is essential for language learning because it allows one to understand the psychological processes that occur when someone speaks, reads, writes, or listens, as well as the processes that happen when someone says, reads, and reports. This understanding allows one to see alternative psychological solutions to language learning problems